α-Amino Acids and Peptides as Bifunctional Reagents: Carbocarboxylation of Activated Alkenes via Recycling CO - Liao, Li-Li; Cao, Guang-Mei; Jiang, Yuan-Xu; Jin, Xing-Hao; Hu, Xin-Long; Chruma, Jason J.; Sun, Guo-Quan; Gui, Yong-Yuan; Yu, Da-Gang (Journal of the American Chemical Society, 2021)
Carboxylic acids, including amino acids (AAs), have been widely used as reagents for decarboxylative couplings. In contrast to previous decarboxylative couplings that release CO₂ as a waste byproduct, herein we report a novel strategy with simultaneous utilization of both the alkyl and carboxyl components from carboxylic acids. Under this unique strategy, carboxylic acids act as bifunctional reagents in the redox-neutral carbocarboxylation of alkenes. Diverse, inexpensive, and readily available α-AAs take part in such difunctionalizations of activated alkenes via visible-light photoredox catalysis, affording a variety of valuable but otherwise difficult to access γ-aminobutyric acid derivatives (GABAs). Additionally, a series of dipeptides and tripeptides also participate in this photocatalytic carbocarboxylation. Although several challenges exist in this system due to the low concentration and quantitative amount of CO₂, as well as unproductive side reactions such as hydrodecarboxylation of the carboxylic acids and hydroalkylation of the alkenes, excellent regioselectivity and moderate to high chemoselectivity are achieved. This process features low catalyst loading, mild reaction conditions, high step and atom economy, and good functional group tolerance, and it is readily scalable. The resulting products are subject to efficient derivations, and the overall process is amenable to applications in the late-stage modification of complex compounds. Mechanistic studies indicate that a carbanion is generated catalytically and it acts as the key intermediate to react with CO₂, which is also generated catalytically in situ and thus remains in low concentration. The overall transformation represents an efficient and sustainable system for organic synthesis, pharmaceutics, and biochemistry.